Simple Method of Sales Profitability Forecasting in an Enterprise - Witkowski, Marek (Prosta metoda prognozowania rentowności sprzedaży w przedsiębiorstwie, 2010)
The return on sale (ROS) is one of the most common used indexes (ratios) to estimate the effectiveness of running an enterprise. This index in general - is estimated "at point" having information about the sales income and financial results of the company. It does not, however, include the growing path of a company, which means that the results of a work done by an enterprise in time t are not influenced by the earlier results. So, to make up for that inconvenience, we propose to use the regression model with variable parameters, in which the explained variable are total operative costs and the explanatory variable are sales incomes.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2010; Nr 91, s. 186-194
Keywords: forecast; return of sales; regression model with variable parameters